2004
DOI: 10.2174/1389557043403747
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development in the Field of Dual COX / 5-LOX Inhibitors

Abstract: Cyclooxygenases and lipoxygenase are key enzymes in the arachidonic acid metabolism. Dual inhibitors are drugs able to block both the COX and the 5-LOX metabolic pathways. Compared to COX or LOX pathways single inhibitors, dual inhibitors present at least two major advantages. First, dual inhibitors, by acting on the two major arachidonic acid metabolic pathways, possess a wide range of anti-inflammatory activities. Secondly, dual inhibitors appear to be almost exempt from gastric toxicity, which is the most t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…In contrast, the nonselective COX-1/COX-2 inhibitor piroxicam decreased prostaglandin production from canine mast cells, but the production of leukotrienes appeared to increase following treatment. This is consistent with previous data suggesting that inhibition of COX pathways may induce an upregulation of 5-LOX based leukotrienes (Julemont et al, 2004; Mao et al, 2004). In contrast, NDGA, a selective 5-LOX inhibitor induced the opposite effect on canine mast cells, decreasing leukotriene production while increasing prostaglandin production.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, the nonselective COX-1/COX-2 inhibitor piroxicam decreased prostaglandin production from canine mast cells, but the production of leukotrienes appeared to increase following treatment. This is consistent with previous data suggesting that inhibition of COX pathways may induce an upregulation of 5-LOX based leukotrienes (Julemont et al, 2004; Mao et al, 2004). In contrast, NDGA, a selective 5-LOX inhibitor induced the opposite effect on canine mast cells, decreasing leukotriene production while increasing prostaglandin production.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies evaluating inhibition of 5-LOX by Zileuton® demonstrated enhanced thromboxane A2 production and increased platelet aggregation (Wu et al, 2003), implying a similar “shunting” of lipid mediators to the COX pathway after 5-LOX inhibition. Given the potential paradoxical effects of COX-only or LOX-only inhibition, dual inhibitors of COX and LOX have been suggested to be potentially more useful for the clinical management of inflammatory conditions without gastrointestinal toxicity (Julemont et al, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…[72][73][74][75][76][77][78]; 3) thiophene derivatives (RWJ-63556) [79,80]; 4) pyrazoline derivatives (phenidone, BW-755C) [81]; 5) pyrrolizine derivatives (licofelone, etc.) [82][83][84][85].…”
Section: Drugs Able To Inhibit Both Cyclooxy-genases (Cox-1 And/or Comentioning
confidence: 99%
“…A number of studies have demonstrated that leukotrienes are important regulators of cancer cell proliferation and cause apoptosis in non-cancer cells [41], [42], [43], [44], [45] and [46]. Since, AA is metabolized via LOX-5 into leukotrienes, specific inhibition of LOX-5 may shunt the AA metabolism by LOX-5 leading to the decreased formation of leukotrienes.…”
Section: Discussionmentioning
confidence: 99%